Characteristics of interaction between parents and children with visual impairment at preschool age - Martac, Valentina; Vučinić, Vesna; Anđelković, Marija; Vladisavljević, Zorica (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Parenting is a dynamic process influenced by the behavior of both children and parents. Behavior of children with visual impairment is characterized by the absence of language which involves smiling and looking, calming down when focusing on voice, unusual posture, stereotyped behavior, blank face, which can all interfere with parent-child interaction. Objective. The aim of this paper was to determine the characteristics of interaction between mothers and children with visual impairment and multiple disabilities. Methods. The research included a total of thirteen mother-child pairs. Five children had a visual impairment, while eight had both a visual impairment and another comorbid condition. The children were between 10 and 68 months of age (M = 31.62, SD = 19.08). The characteristics of interaction between mothers and children with visual impairment and multiple disabilities were assessed by analyzing videos, while Parenting Interactions with Children – Checklist of Observations Linked to Outcomes – PICCOLO was used to record the observed behaviors. Results. Interaction between parents and children with visual impairment and multiple disabilities was satisfactory in three domains: Affection, Responsiveness, and Encouragement. Conclusion. The biggest problem for parents was finding a way to teach their child some activities or to provide information about the environment.